The TWI workbook : essential skills of supervisors - Graupp, Patrick; Wrona, Robert J. (CRC Press, 2016)
Since the publication of its Shingo Prize-winning predecessor, TWI programs have seen steady growth in usage. As a true understanding of Standard Work has developed, the need for the TWI skills as fundamental tools to achieve Lean objectives has been solidified. The TWI Workbook: Essential Skills for Supervisors, Second Edition has been completely updated to the latest terminology and practice. This edition includes revised forms and tools, as well as new examples that illustrate current day TWI practice. Emphasizing the importance of accident and injury prevention, this edition includes an entirely new section on Job Safety, a fourth TWI module that was developed in Japan using the identical TWI methodology of the original three programs introduced in the original work.